Siglec Receptors Modulate Dendritic Cell Activation and Antigen Presentation to T Cells in Cancer - Wang, Jinyu; Manni, Michela; Bärenwaldt, Anne; Wieboldt, Ronja; Kirchhammer, Nicole; Ivanek, Robert; Stanczak, Michal; Zippelius, Alfred; König, David; Rodrigues Manutano, Natalia; Läubli, Heinz (Frontiers in Cell and Developmental Biology, 2022)
Interactions between sialylated glycans and Siglec receptors have been recently described as potential new immune checkpoint that can be targeted to improve anticancer immunity. Myeloid cells have been reported to express a wide range of different Siglecs, however their expression and functions on cancer-associated dendritic cells (DCs) were not fully characterized. We found that classical conventional DCs (cDCs) from cancer patient samples have a high expression of several inhibitory Siglecs including Siglec-7, Siglec-9 and Siglec-10. In subcutaneous murine tumor models, we also found an upregulation of the inhibitory Siglec-E receptor on cancer-associated cDCs. DC cell lines and BMDCs with expression of these inhibitory Siglecs showed impaired maturation states on transcriptome and protein level. Furthermore, ablation of these inhibitory Siglecs from DCs enhanced their capability to prime antigen specific T cells and induce proliferation. Our work provides a deeper understanding of the influence of inhibitory Siglecs on DCs, and reveals a potential new target to improve cancer immunotherapy.